1978
DOI: 10.1063/1.324782
|View full text |Cite
|
Sign up to set email alerts
|

Grain-size effects on microwave ferrite magnetic properties

Abstract: A general review is given on effects and controls of grain size, so far documented, concerning both soft and microwave ferrites, while referring to the findings of ceramists as well as to the representative models available for initial permeability spectra and for microwave parameters, such as ΔHk and ΔHeff. As an illustrative example, a briefing is given on narrow linewidth CaV-garnet families, finding an ever-increasing usage, with reduced loss resulting from the grain size being intentionally increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The increase is generally attributed to some aspects of the microstructure, such as porosity, grain size, grain size distribution, or anisotropy in the randomly oriented crystallites. 9,14 On the other hand, the off-resonance effective linewidth, especially at high field, is not affected by two-magnon scattering and can be much smaller. The spin wave linewidth represents the relaxation rate of the renormalized spin wave modes that exhibit a threshold loss effect under parametric excitation.…”
Section: Microwave Linewidth Parameters and Measurement Overviewmentioning
confidence: 99%
“…The increase is generally attributed to some aspects of the microstructure, such as porosity, grain size, grain size distribution, or anisotropy in the randomly oriented crystallites. 9,14 On the other hand, the off-resonance effective linewidth, especially at high field, is not affected by two-magnon scattering and can be much smaller. The spin wave linewidth represents the relaxation rate of the renormalized spin wave modes that exhibit a threshold loss effect under parametric excitation.…”
Section: Microwave Linewidth Parameters and Measurement Overviewmentioning
confidence: 99%
“…Pal et al [32] reported high coercivity in soft spinel ferrite materials with nanosized dimensions as compared to that in micron-sized ones. Inui and Ogasawara [33] found the inverse proportion of coercivity to grain size in multidomain grains. This is because the enlargement of the grains takes place with increasing sintering temperature in such a way that the larger grains contain more domain walls, enhancing the wall movement contribution to magnetization or demagnetization [33,34].…”
Section: Resultsmentioning
confidence: 98%
“…Inui and Ogasawara [33] found the inverse proportion of coercivity to grain size in multidomain grains. This is because the enlargement of the grains takes place with increasing sintering temperature in such a way that the larger grains contain more domain walls, enhancing the wall movement contribution to magnetization or demagnetization [33,34]. In fact, wall movement requires a lower energy than the rotation of domains.…”
Section: Resultsmentioning
confidence: 98%
“…Large grain size reduces the number of grain boundaries in the sample and increases initial permeability. Globus proposed a model for initial permeability, in which the domain wall is pinned to grain surface, and reversible wall motion is caused by wall bulging . As per this model, initial permeability varies linearly with grain size and saturation magnetization.…”
Section: Factors Influencing Initial Permeabilitymentioning
confidence: 99%